Chemical profile and antimicrobial activity of essential oil and methanol extract from peels of four Durio zibethinus L. varieties - Nor Hisam, Zamakshshari; Ahmed, Idris Adewale; Nur Alyaa, Mat Didik; Muhammad Nazil Afiq, Nasharuddin; Najihah, Mohd Hashim; Rosazlin, Abdullah (Springer, 2022)
Durio zibethinus L. (durian) belongs to the Malvaceae family. It is known as the “King of Tropical Fruit” because of its unique characteristics. The edible part of durian, however, is only about 33% of the fruit while the non-edible parts such as the seed and peels (rinds) are considered as fruit waste responsible for environmental pollution. Thus, the present study was carried out to compare the percentage yields and volatile components from methanol extract and essential oils of the peels of four varieties of durian (Raja Kunyit [D197], Hajah Hasmah [D168], Sultan [D24], and Golden Bun [D13]). The antimicrobial activity of all the extracts and their volatile chemical constituents were also evaluated. Cold maceration was used for the solvent (methanol) extraction. The essential oil extraction was carried out using hydro-distillation and solventfree microwave extraction (SFME) methods. The antimicrobial activity was evaluated against selected microbes using the well difusion method while the characterization of chemical constituents in the essential oils and crude methanolic extracts was carried out using gas chromatography-mass spectrometry (GC–MS). The highest yields of essential oils were obtained from D24 which were 0.030% and 0.014% from SFME and hydro-distillation extraction, respectively, while the highest and most signifcant (p<0.05) yield of methanol extract (8.79%) was obtained from D197. From the GC–MS analysis, butanoic acid was the major compound in the essential oil of durian peels in the four varieties of durians evaluated. Besides butanoic acid, 1-tridecene, 1-pentadecene, and 1-heptadecene were also present in the four varieties. The D168 possesses strong activity against three bacteria (Bacillus subtilis, Staphylococcus aureus, and Pseudomonas aeruginosa). More novel extraction techniques, bioactivity assays, and characterization are, however, recommended to further explore the potential benefts of durian peels.